The theology of the New Testament according to its major witnesses, Jesus, Paul, John - Kummel, Werner Georg, 1905-; Steely, John (Nashville, TN Abingdon, 1973)
Includes indexres.
Translation of " Die Theologie des Neuen Testaments nach seinen Haupzeugen Jesus, Paulus, Johannes". Donated by John Dickson, Dec. 2002.
Keywords: Bible. N.T. -- theology